Relationship between destination affect and intention to visit: the case of destination dislike - Renzi, M. F.; Loureiro, S. M. C.; Toni, M.; Panchapakesan, P. (47th International EMAC conference-People Make Marketing, 2018)
This paper builds on consumer-brand relationships with an application in the destination context. By analysing the main theoretical contributions, we propose a model in order to shed light on the antecedents of Destination Loyalty in two countries: Portugal and Italy. A proposed model has been tested through a quantitative survey, by administering a questionnaire to an Italian and a Portuguese sample. The two samples were selected consistently with the proportions (in terms of gender and age) of in each city population. The PLS approach was employed to test the model with a twofold objective: assessing the adequacy of the measurements by evaluating the reliability of the individual measures and the discriminant validity of the constructs; appraising the structural model. Although the majority of the hypotheses have been confirmed for both the samples, our findings underline differences among the two nationalities and proposes further field of investigations.